Perencanaan Sistem Pneumatik Sebagai Penggerak pada Pintu Gerbong Kereta - Jones Victor Tuapetel; Rohdi Narwalutama (Universitas Indraprasta PGRI Jakarta, 2022)
Pneumatic system is a system that is used as an automation system today by using air as its driver. The use of pneumatic systems in this planning aims to be used to open and close the doors of train cars. To get the pneumatic design as desired, a design and simulation is made using Festo Fluid Simulator. The result of the planning of a pneumatic system circuit produces a circuit according to its function. Based on calculations performed on force (1170.25 N) with speed (0.22 m/s) produced (5.68 s) to open the door and at force (1562.95 N) with speed (0.25 m/s) generated (4.68 s) to close the door. Simulation on Festo Fluid Simulator with the addition of one way valve (63%) with its mounting influence to close the door resulted in speed (0.25 m/s) and one way valve installation effect (61%) to open resulting in speed (0.21 m/s).